The Axis Contract for the regeneration of fragile territories. An experiment along the Civitavecchia Capranica Orte railway line - Amato, Chiara; Cerasoli, Mario (TeMA - Journal of Land Use, Mobility and Environment, 2025)
The article explores the revitalization of Italy's "inner areas" - —fragile territories facing challenges such as depopulation, abandonment, and a lack of essential services, primarily due to limited mobility. The enhancement of secondary and disused railways is proposed as a tool for territorial rebalancing, to be achieved through multilevel governance that integrates spatial planning, interinstitutional cooperation, and the strategic allocation of financial and economic resources. This approach aims to move beyond sectoral perspectives on infrastructure networks. The Axis Contract is introduced as an integrated framework linking urban planning and mobility, centered on the right to mobility and the empowerment of local communities. The article is structured into three parts: the first examines the relationship between territory, mobility, and infrastructure policies; the second analyzes the French Contrat d’axe model and its applicability in Italy; and the third presents the results of an interdisciplinary study on the reactivation of the Civitavecchia -Capranica - Orte railway line. The findings confirm that the Axis Contract is an effective tool for integrating urban and mobility planning, addressing accessibility needs, and promoting the sustainable rebalancing of territories.